2017
DOI: 10.18632/oncotarget.15834
|View full text |Cite
|
Sign up to set email alerts
|

KPNB1-mediated nuclear import is required for motility and inflammatory transcription factor activity in cervical cancer cells

Abstract: Karyopherin β1 is a nuclear import protein involved in the transport of proteins containing a nuclear localisation sequence. Elevated Karyopherin β1 expression has been reported in cancer and transformed cells and is essential for cancer cell proliferation and survival. Transcription factors such as NFĸB and AP-1 contain a nuclear localisation sequence and initiate the expression of multiple factors associated with inflammation and cancer cell biology. Our study investigated the effect of inhibiting nuclear im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 58 publications
0
22
0
Order By: Relevance
“…mDia1 interacts with proteins involved in nuclear import and protein folding in MB, suggesting novel stage-specific roles for mDia1 in MB. It's interaction with proteins regulating nuclear import such as Kpnb1, Hsp90ab1and Hsp90aa1 (Hasse and Fitze, 2016;Stelma and Leaner, 2017;Zhong et al, 2014) suggests that mDia1 might shuttle between the nucleus and cytoplasm, similar to mDia2 (Miki et al, 2009;Shao et al, 2015). Consistent with its scaffolding properties (Wallar and Alberts, 2003), mDia1 associates with chaperones such as Hsp90b1, Hsp90ab1, Hsp90aa1 (Schopf et al, 2017), suggesting a potential involvement in regulating protein folding.…”
Section: Analysis Of Mdia1-interacting Proteins Reveals Stage-specifimentioning
confidence: 87%
“…mDia1 interacts with proteins involved in nuclear import and protein folding in MB, suggesting novel stage-specific roles for mDia1 in MB. It's interaction with proteins regulating nuclear import such as Kpnb1, Hsp90ab1and Hsp90aa1 (Hasse and Fitze, 2016;Stelma and Leaner, 2017;Zhong et al, 2014) suggests that mDia1 might shuttle between the nucleus and cytoplasm, similar to mDia2 (Miki et al, 2009;Shao et al, 2015). Consistent with its scaffolding properties (Wallar and Alberts, 2003), mDia1 associates with chaperones such as Hsp90b1, Hsp90ab1, Hsp90aa1 (Schopf et al, 2017), suggesting a potential involvement in regulating protein folding.…”
Section: Analysis Of Mdia1-interacting Proteins Reveals Stage-specifimentioning
confidence: 87%
“…Lastly, IPZ treatment significantly increased PUMA expression at both mRNA and protein levels ( Figure 3C,D), suggesting that IPZ enhances PUMA expression by preventing ∆Np63 nuclear import. Since KPNB1 blockage was reported to block c-JUN nuclear import [29], the localization of c-JUN was also investigated ( Figure S3). Consistent with previous reports [29], the nuclear levels of c-JUN were inhibited by IPZ ( Figure S3).…”
Section: Ipz Abolishes the Transcriptional Silencing Of Puma By Blockmentioning
confidence: 99%
“…Since KPNB1 blockage was reported to block c-JUN nuclear import [29], the localization of c-JUN was also investigated ( Figure S3). Consistent with previous reports [29], the nuclear levels of c-JUN were inhibited by IPZ ( Figure S3). Of utmost importance is the examination of TCGA RNA-seq datasets that further showed that the expression levels of PUMA are inversely related to the levels of p63 and not of the activator protein 1 (AP-1) family, including c-JUN ( Figure 3E,F and Figure S2B,C).…”
Section: Ipz Abolishes the Transcriptional Silencing Of Puma By Blockmentioning
confidence: 99%
“…The dynamic reorganization of the actin cytoskeleton is a prerequisite for the morphology, migration and invasion of cancer cells. 56,57 All these proteins are known as building blocks for cell formation and survival. 55 Moreover, up-regulation of importin subunit beta-1 promotes tumour cell proliferation and predicts poor prognosis in non-small lung, cervical, glioma and gastric cancer.…”
Section: Anova (P)mentioning
confidence: 99%
“…55 Moreover, up-regulation of importin subunit beta-1 promotes tumour cell proliferation and predicts poor prognosis in non-small lung, cervical, glioma and gastric cancer. 56,57 All these proteins are known as building blocks for cell formation and survival.…”
Section: Anova (P)mentioning
confidence: 99%